Design of a scheme to protect transformers against bushing insulation damage, in order to modernize energy facilities - Sakhno, Oleksandr; Shylo, Serhii; Odiyaka, Kostiantyn; Skrupska, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2025)
This study's object is a relay protection scheme against damage to transformers (autotransformers) and 35–750 kV shunt reactors as a result of bushing insulation breakdown. The study investigates the possibility of improving the efficiency of the relay protection of transformer equipment (TrE). The task relates to the widespread application of outdated TrE protection schemes and devices that account for their high cost, low operational efficiency, and may even harm TrE. This paper reports the results of investigating current signals from the measuring terminals of bushings and formulates basic requirements for implementing modernized protection schemes based on microprocessor monitoring unit. The proposed protection scheme modernization demonstrates improved operational characteristics: increased safety for personnel and equipment, reduced probability of false trips, decreased weight and dimensions, as well as cost. These characteristics were achieved by using a microprocessor device, reducing the length of measurement circuits, excluding matching transformers from the scheme, applying coupling devices with protection circuit. The effectiveness of using software filtering of current signals based on the discrete Fourier transform algorithm has been proposed and proven for excluding influence currents on the resulting unbalance vector. The inexpediency of accounting for all, except the 1st harmonic, components of insulation currents was demonstrated. The normalized value of the unbalance, while using full signals, was 14%, instead of 1.15%. The results could be used to manufacture and operate relay protection schemes and devices against 35–750 kV TrE damage caused by breakdown of bushing insulation to improve the reliability of power facilities